Late effect of an embolized coronary stent in the lower extremities - Mauricio Gonzalez-Urquijo; Francisco Valdes; Leopoldo Marine; Jose Francisco Vargas; Michel Bergoeing (Annals of Vascular Surgery - Brief Reports and Innovations)
Purpose: To report a late complication involving an embolized stent that migrated into the peripheral circulation during an emergency coronary intervention. Case Report: A 69-year-old man with a history of myocardial infarction 12 years prior, during which he experienced prolonged cardiac arrest following a failed coronary stenting attempt and subsequent aorto-coronary bypass surgery, presented to the emergency department with acute limb ischemia in the right lower limb. A CT angiogram revealed complete occlusion of the popliteal artery and a hyperdense image at the tibioperoneal trunk. Popliteal artery exploration and embolectomy successfully restored proximal blood flow; however, a firm occlusion at the tibioperoneal trunk necessitated an arteriotomy. This procedure uncovered a coronary stent adhered to the endothelium, which was removed via endarterectomy. The patient was prescribed rivaroxaban for six months. At a six-year follow-up, he remains well and asymptomatic, continuing on aspirin and a reduced dose of rivaroxaban. Conclusion: This case underscores the importance of monitoring long-term complications following coronary interventions and highlights the need for vigilance in managing patients at risk for device embolization.